PECULIARITIES OF THE CLINICAL COURSE IN PATIENTS WITH VARIOUS PURULENT-INFLAMMATORY DISEASES OF THE MAXILLOFACIAL REGION WHO HAD HEPATITIS B (World Bulletin of Public Health, 2022)
On the material of 60 cases of patients with different purulent-inflammatory diseases of maxillofacial region having hepatitis B . This article demonstrates the severity of the course and high prevalence of acute inflammatory process in the maxillofacial region, as well as the necessity of pathogenetic therapy of hepatitis B in the complex treatment of the discussed group of patients
Keywords: hepatitis B; purulent inflammatory diseases; putrefactive necrotic processes; region